Educação financeira e juventudes: análise do bem-estar e dos comportamentos financeiros dos jovens católicos da Diocese de Toledo-Pr - Alves, Ana Carolina Fernandes (2021)
This study aimed to analyze the perception of the Financial Education theme by young Catholics, participants in youth groups in the Diocese of Toledo-PR. Specifically, we sought to i) describe the socioeconomic characteristics of young Catholics in the Diocese of Toledo; ii) verify the level of financial well-being of the group of individuals analyzed in the research; iii) to identify the presence of heuristics and behavioral biases in the choices regarding the finances of the young people surveyed iv) investigate whether the young people surveyed have performed activities related to finance in their weekly meetings.For this purpose, primary data were used, which were collected through the application of questionnaires and semi-structured interviews. The analyzes were performed using descriptive statistics tools and the calculation of the level of financial well-being of the young people surveyed according to the methodology developed by the Consumer Financial Protection Bureau (CFPB). As a result, it was found that the average level of financial well-being of the young people surveyed was 55 points, higher than the national average of 47 points identified by the SPC survey (2019).With regard to heuristics and behavioral biases, their influence on the choices of youths and the fact that young people with higher degrees of financial well-being tend to make less biased decisions were observed. Finally, from the interviews, it was observed that the groups of young Catholics are configured as favorable spaces for holding discussions on finance. It was concluded, therefore, that an educational work aimed at young people is necessary for the responsible use of their financial resources.